Midgut Mitochondrial Function as a Gatekeeper for Malaria Parasite Infection and Development in the Mosquito Host - Luckhart, Shirley; Riehle, Michael A. (Frontiers in Cellular and Infection Microbiology, 2020)
Across diverse organisms, various physiologies are profoundly regulated by mitochondrial function, which is defined by mitochondrial fusion, biogenesis, oxidative phosphorylation (OXPHOS), and mitophagy. Based on our data and significant published studies from Caenorhabditis elegans, Drosophila melanogaster and mammals, we propose that midgut mitochondria control midgut health and the health of other tissues in vector mosquitoes. Specifically, we argue that trade-offs among resistance to infection, metabolism, lifespan and reproduction in vector mosquitoes are fundamentally controlled both locally and systemically by midgut mitochondrial function.